Structural and biological studies on bacterial nitric oxide synthase inhibitors - Holden, Jeffrey K. (National Academy of Sciences, 2013)
Nitric oxide (NO) produced by bacterial NOS functions as a cytoprotective agent against oxidative stress in Staphylococcus aureus, Bacillus anthracis, and Bacillus subtilis. The screening of several NOS-selective inhibitors uncovered two inhibitors with potential antimicrobial properties. These two compounds impede the growth of B. subtilis under oxidative stress, and crystal structures show that each compound exhibits a unique binding mode. Both compounds serve as excellent leads for the future development of antimicrobials against bacterial NOS-containing bacteria.